Hubungan Asupan Energi dan Zat Gizi Makro serta Durasi Tidur dengan Status Gizi Mahasiswa Baru Fakultas Kesehatan Masyarakat Universitas Airlangga selama Kuliah Online: Association between Energy and Macronutrient Intake and Sleep Duration with Nutritional Status of New Students of the Faculty of Public Health, Universitas Airlangga during Online Courses - Chrysoprase Thasya Abihail; Ketut Herlin Simanoah; Lailatul Muniroh (Amerta Nutrition, 2023)
Background: Learning from home is a government policy to decrease the number of COVID-19 in Indonesia. This condition requires university students to adapt to new technology that has the potential to affect sleep and consumption patterns that will influence their nutritional status. Objectives: The purpose of the study was to analyze the relationship between energy, macro-nutrient consumption, and sleep duration with the nutritional status of new students of FKM UNAIR. Methods: The research was an observational study with a cross-sectional design. A total of 55 students were randomly selected to be the research sample. Research data collection was done by using Google Forms. Research data were analyzed using the Spearman correlation test. Results: Most of the new FKM UNAIR students were female (87.3%), had sleep duration <7 hours/day (56.4%), and had normal nutritional status (69.1%). Most of the respondents had less intake of energy (47.3%), fat (54.5%), carbohydrates (60%), and excess protein intake (52.7%). The statistical tests showed that energy intake (p-value = 0.426), macronutrients including protein (p-value = 0.170), fat (p-value = 0.129), and carbohydrates (p-value = 0.884), also sleep duration (p-value = 0.190) was not related to the nutritional status of new students of FKM UNAIR. Conclusions: There was no correlation between energy intake, macronutrients, and sleep duration with the nutritional status of new FKM UNAIR students. Instead, students should pay attention to the duration of sleep and intake following the principles of balanced nutrition.